Approaches to the financial statements and to their Influence on business law - Tabra Ochoa, Edison Paul (2018)
The academic article has the main purpose to explain theory and qualities of financial statements and relation to business law. From a legal perspective, the paper works fundaments of financial statements and role in commercial, tax, and criminal law. Besides, it makes a lot of clarifications about its work in order to be clearly understood by readers.